THE LINES APPLY RESEARCH IN THE ACCONTING RESEARCH PROGRAMME - Polar Falcón, Ernesto Augusto (2010)
This article discusses the concepts of lines of investigation “which are explained in the development of the Research Studies Project, which promotes year by year the Research of San Marcos and the development of research, applying the” sublines of research. “The first are permanent and connecte with the development of research work of the Interamerican Accounting Conference - CIC, and the latter defines the current accounting issues on which they must develop those research works that defined our Alma Mater as “Research Study Projects” using the methods of CON/CON - INS/CON - NO/NO: With asignation for Research and incentives to researchers, no allocation for research and incentives to researchers and no allocation to the no incentive to research and researcher. This process will be beneficial for the development of our School of Accounting Studies.